2003
DOI: 10.1128/jcm.41.4.1747-1749.2003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Monoclonal Antibodies to Lipopolysaccharide for Antigenic Analysis of Coxiella burnetii

Abstract: Antigenic differences among Coxiella burnetii strains were analyzed. The monoclonal antibodies against the lipopolysaccharide outer core did not react with the strains containing a QpRS plasmid or with plasmidless strains, whereas they reacted with strains containing a QpH1 or QpDV plasmid. C. burnetii isolates could be divided into two groups immunologically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Several PI-LPS specific mAbs have been developed for analysis of antigenicity of immunogenic components of C. burnetii LPS and detection of the virulent form of C. burnetii (3336). Hotta et al (34) reported generation of 19 PI-LPS specific mAbs and demonstrated that these mAbs were able to be separated into three groups based on their reactivity with O-polysaccharide chains (27 kDa of PI-LPS), O-polysaccharide chains (15 to 27 kDa of PI-LPS) and outer-core oligosaccharides (14 kDa of PI-LPS).…”
Section: Discussionmentioning
confidence: 99%
“…Several PI-LPS specific mAbs have been developed for analysis of antigenicity of immunogenic components of C. burnetii LPS and detection of the virulent form of C. burnetii (3336). Hotta et al (34) reported generation of 19 PI-LPS specific mAbs and demonstrated that these mAbs were able to be separated into three groups based on their reactivity with O-polysaccharide chains (27 kDa of PI-LPS), O-polysaccharide chains (15 to 27 kDa of PI-LPS) and outer-core oligosaccharides (14 kDa of PI-LPS).…”
Section: Discussionmentioning
confidence: 99%
“…The others were stocked and/or maintained at NIID. The inactivated Coxiella burnetii cultures (23) and Wolbachia pestis (24) genomic DNA were kindly provided by Drs. Hideto Fukushi (Department of Veterinary Medicine, Faculty of Applied Biological Science, Gifu University, Gifu, Japan) and Tetsuhiko Sasaki (Department of Biological Science, Graduate School of Science, University of Tokyo, Tokyo, Japan), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Complete elimination from an immunocompetent host leads to the phase II developmental stage. 5 As others have done previously, 3,4,8,11,12,14,15 we employed the specificity of monoclonal antibodies (Mabs) as probes to detect antigenic differences. We prepared several Mabs and used them to differentiate numerous isolates.…”
Section: Introductionmentioning
confidence: 99%